2016
DOI: 10.1080/19420862.2016.1160989
|View full text |Cite
|
Sign up to set email alerts
|

XGFR*, a novel affinity-matured bispecific antibody targeting IGF-1R and EGFR with combined signaling inhibition and enhanced immune activation for the treatment of pancreatic cancer

Abstract: The epidermal growth factor receptor (EGFR) and the insulin-like growth factor-1 receptor (IGF-1R) play critical roles in tumor growth, providing a strong rationale for the combined inhibition of IGF-1R and EGFR signaling in cancer therapy. We describe the design, affinity maturation, in vitro and in vivo characterization of the bispecific anti-IGF-1R/EGFR antibody XGFR*. XGFR* is based on the bispecific IgG antibody XGFR, which enabled heterodimerization of an IGF-1R binding scFab heavy chain with an EGFR-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“… 110 Bispecific antibody with EGFR (GA201) and IGF-1R (R1507) specificities     XGFR*IGF-1R and EGFRReducedCoexpression with GnT III and α-ManII in CHO cells (GlycoMAb Technology)Enhanced tumor inhibition over fucosylated bispecific orthotopic Mia-PaCa2 pancreatic cancer xenograft model in SCID miceSchanzer et al. 130 Bispecific antibody with EGFR (GA201) and affinity-matured IGF-1R (R1507) – F13B5 specificities     JNJ-61186372EGFR and c-MetReduced (<10%)CHO cells with low level of fucoseEnhanced xenograft tumor inhibition in nude mouse over control and afucosylated IgG2 isotypeGrugan et al. 109 Bispecific human IgG1     Ifabotuzumab/KB004/IIIA4EPHA3afucosylatedFUT8 −/− CHO cells (Potelligent® Technology)Enhanced tumor growth inhibition over control antibody in DU145 or 22Rv1 xenograft miceVail et al.…”
Section: Enhanced Adcc Activities By Afucosylated Antibodies In In VImentioning
confidence: 99%
“… 110 Bispecific antibody with EGFR (GA201) and IGF-1R (R1507) specificities     XGFR*IGF-1R and EGFRReducedCoexpression with GnT III and α-ManII in CHO cells (GlycoMAb Technology)Enhanced tumor inhibition over fucosylated bispecific orthotopic Mia-PaCa2 pancreatic cancer xenograft model in SCID miceSchanzer et al. 130 Bispecific antibody with EGFR (GA201) and affinity-matured IGF-1R (R1507) – F13B5 specificities     JNJ-61186372EGFR and c-MetReduced (<10%)CHO cells with low level of fucoseEnhanced xenograft tumor inhibition in nude mouse over control and afucosylated IgG2 isotypeGrugan et al. 109 Bispecific human IgG1     Ifabotuzumab/KB004/IIIA4EPHA3afucosylatedFUT8 −/− CHO cells (Potelligent® Technology)Enhanced tumor growth inhibition over control antibody in DU145 or 22Rv1 xenograft miceVail et al.…”
Section: Enhanced Adcc Activities By Afucosylated Antibodies In In VImentioning
confidence: 99%
“…Dual targeting strategies with bispecific agents have been classified into two types: i) those that directly act on target molecules, such as bispecific antibodies and ii) those that depend on targets for delivering an active moiety to killing tumor cells, such as bispecific immunotoxins or fusion proteins. A number of bispecific antibodies targeting both EGFR and IGF-1R (EI-04 and XGFR) have demonstrated superior antitumor activity in preclinical models (33,34), and bispecific immunotoxins/fusion proteins developed by Vallera et al also demonstrated either enhanced antitumor activity or broader spectrum of reactivity than the mono-specific molecules (35)(36)(37). EGF-LDP-IGF-AE is a bispecific enediyne-energized fusion protein that was constructed by fusing the natural ligands of EGFR and IGF-1R (EGF and IGF-1) to an enediyne antibiotic lidamycin (LDM; C1027) with potent antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we present a case study on the bispecific XGFR antibody 46 comprising a Fab for monovalent binding of epidermal growth factor receptor (EGFR) and a single chain Fab specific for human insulin-like growth factor 1 receptor (IGF-1R) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%